The Development Story of Toyama : Reshaping Compact and Livable Cities - Arai, Yuko (World Bank, Washington, DC, 2021)
Toyama City, one of the World Bank TDLC City Partnership Program cities, has become synonymous with the idea of a compact and livable city in Japan. It is a pleasant regional city with a population of about 420,000, situated in a dramatic landscape between the steep Tateyama mountain range on the east and deep Toyama Bay on the north side. The city has been consistently ranked among the best cities to live within the Hokuriku region. This report illustrates the compact city development in the city, along with series of cross-sectoral case studies on disaster risk management, waste management, inclusive community engagement, and a comprehensive resilient city approach.